LENGTH-WEIGHT RELATIONSHIPS FOR 14 FISH SPECIES OF NAPO RIVER BASIN, PERUVIAN AMAZON - GARCIA-AYALA, James Raúl (2020)
This work presents the length-weight relationships of 14 species of fish of the Napo River basin. Fish collections were carried out between 2012 and 2014, using gill nets and seine. A total of 1896 specimens, belonging to 14 species and five orders were analyzed. The allometric coefficient b ranged from 2.69 to 3.78. A new record of length-weight relationship is presented for Curimata cisandina (Allen, 1942). The comparisons with other Amazonian studies indicated differences in the parameters a and b of LWR with this study for the species Triportheus angulatus (Spix & Agassiz, 1829), Mylossoma duriventre (Cuvier, 1818), Roeboides myersii Gill, 1870 and Pellona castenaena Valenciennes, 1847 and only parameter b for Psectrogaster amazonica. The results presented in this work contribute to a better knowledge of fish resources in the region of the Peruvian Amazon, especially in the Napo River basin.